Analysis of Customer Satisfaction Factors on Social Media Instagram Bank Syariah Indonesia - Cahyani, Merlinda Putri Eka; Nurhidayati, Maulida; Hendayanti, Ni Putu Nanik; Mokan, Zaimudin Al Mahdi (Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: Bank Syariah Indonesia, through the official Instagram account @banksyariahindonesia always provides information regarding messages, advertisements, promotions, and services, but according to some customers, this is inaccurate and less effective. Therefore this study aims to analyze the influence of customer satisfaction factors on Instagram social media of Indonesian Islamic banks. Research Methods: This research method uses quantitative research methods. The population in this study were followers of Bank Syariah Indonesia's Instagram. The sample size was 100 respondents with a purposive sampling method. The data collection method used a questionnaire. The data was analyzed using SPSS 22 software. Results: The results showed that the quality of information, complaint handling, and promotion through social media Instagram affected customer satisfaction of Bank Syariah Bank Indonesia both partially and simultaneously. Conclusion: This study concludes that for the quality of information, complaint handling, and promotion if it increases, it will also increase the satisfaction of Bank Syariah Indonesia customers.